3D printing technologies for electrochemical energy storage. (October 2017) - Zhang, Feng; Wei, Min; Viswanathan, Vilayanur V.; Swart, Benjamin; Shao, Yuyan; Wu, Gang; Zhou, Chi
Abstract: Fabrication and assembly of electrodes and electrolytes play an important role in promoting the performance of electrochemical energy storage (EES) devices such as batteries and supercapacitors. Traditional fabrication techniques have limitations in controlling the geometry and architecture of the electrode and solid-state electrolytes, which would otherwise compromise the performance. 3D printing, a disruptive manufacturing technology, has emerged as an innovative approach to fabricating EES devices from nanoscale to macroscale, providing great opportunities to accurately control device geometry ( e.g ., dimension, porosity, and morphology) and structure with enhanced specific energy and power densities. Moreover, the "additive" manufacturing nature of 3D printing provides excellent controllability of the electrode thickness with much simplified process in a cost effective manner. With the unique spatial and temporal material manipulation capability, 3D printing can integrate multiple nano-materials in the same print, and multi-functional EES devices (including functional gradient devices) can be fabricated. Herein, we review recent advances in 3D printing of EES devices. We focus on two major 3D printing technologies including direct writing and inkjet printing. The direct material deposition characteristics of these two processes enable them to print on a variety of flat substrates, even a conformal one, well suiting them to applications such as wearable devices and on-chip integrations. Other potential 3D printing techniques such as freeze nano-printing, stereolithography, fused deposition modeling, binder jetting, laminated object manufacturing, and metal 3D printing are also introduced. The advantages and limitations of each 3D printing technology are extensively discussed. More importantly, we provide a perspective on how to integrate the emerging 3D printing with existing technologies to create structures over multiple length scale from nano to macro for EES applications. Graphical abstract: Highlights: The advantages of utilizing 3D printing technologies to fabricate EES devices are highlighted. An overview of employing 3D printing processes in EES area are provided. Materials criteria using 3D printing processes assembly is herein discussed. A mapping of materials and processes with EES conventional fabrication approaches and 3D printing approaches are built.